2008
DOI: 10.1074/jbc.m707411200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Rationale for Selectivity toward N- and C-terminal Oxygen-dependent Degradation Domain Substrates Mediated by a Loop Region of Hypoxia-Inducible Factor Prolyl Hydroxylases

Abstract: Hydroxylation of two conserved prolyl residues in the N-and C-terminal oxygen-dependent degradation domains (NODD and CODD) of the ␣-subunit of hypoxia-inducible factor (HIF) signals for its degradation via the ubiquitin-proteasome pathway. In human cells, three prolyl hydroxylases (PHDs 1-3) belonging to the Fe(II) and 2-oxoglutarate (2OG)-dependent oxygenase family catalyze prolyl hydroxylation with differing selectivity for CODD and NODD. Sequence analysis of the catalytic domains of the PHDs in the light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 37 publications
(49 reference statements)
8
89
0
Order By: Relevance
“…However, the domains are not identical, and there is evidence that there are determinants that convey differences in specificity between the three isoforms. For example, a loop in PHD2 that is distinct from that in PHD3 is responsible for the ability of PHD2 to hydroxylate both the primary and secondary sites of hydroxylation in HIF-1α 96,97 . PHD3, in contrast, displays a marked preference for the primary site of hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the domains are not identical, and there is evidence that there are determinants that convey differences in specificity between the three isoforms. For example, a loop in PHD2 that is distinct from that in PHD3 is responsible for the ability of PHD2 to hydroxylate both the primary and secondary sites of hydroxylation in HIF-1α 96,97 . PHD3, in contrast, displays a marked preference for the primary site of hydroxylation.…”
Section: Discussionmentioning
confidence: 99%
“…K423E substitution, harbored by Patient 3, causes the loss of a positive charged side chain with the acquisition of a complementary charged glutamate, three coding residues from the end of the enzyme. Lys423 is an evolutionary conserved residue in ortholog forms of PHD2 (Mus musculus and Rattus norvegicus, and results for other 2OG oxygenases, 23,24 suggested that removal of the C-terminus of the enzyme actually promotes uncoupled turnover of 2OG. However, due to the lack of the experimental solution of the C-terminal PHD2 structure, 15 it is not possible to anticipate the K423E mutation effects on protein stability and function.…”
mentioning
confidence: 99%
“…Recent kinetic studies also indicate that the preferred substrates for the PHDs are significantly longer than the relatively short peptides (<20-40 residues) used in some analyses [45,47]. Coupled with the structural analyses, it seems likely that the substrate specificity of the PHDs, in part, is determined by regions relatively remote from the iron center, with biochemical assays suggesting the involvement of a substrate binding "lid" [48,49].…”
Section: Hif Hydroxylasesmentioning
confidence: 99%